Charakterisierung und Modellierung der wässrigen Lithium-Luft Batterie - Uhlmann, Christian (Schriften des Instituts für Angewandte Materialien - Werkstoffe der Elektrotechnik, Karlsruher Institut für Technologie / Institut für Angewandte Materialien - Werkstoffe der Elektrotechnik - 2365-8029, 2017)
To estimate the reachable specific energy and power of aqueous Li-air batteries, a physical based model was developed, which for the first time includes the microstructure of Li-air cells. Parameters like solid/liquid interface resistances were quantified with help of a newly developed setup. Simulations based on the developed model revealed that even conservative estimations promise an increase in the specific energy by at least a factor of two compared to present Li-ion batteries.